Outcomes of out-of-hospital extracorporeal membrane oxygenation transfers: significance of initiation site and personnel. (October 2020) - Mihama, Toru; Liem, Spencer; Cavarocchi, Nicholas; Hirose, Hitoshi
Background: Extracorporeal membrane oxygenation is an accepted therapy option for refractory cardiac or respiratory failure. The outcomes of cases initiated at non–extracorporeal membrane oxygenation centers and subsequently transported for management to an extracorporeal membrane oxygenation center require further investigation. Methods: Retrospective institutional review board–approved database research and chart reviews were performed on referrals for extracorporeal membrane oxygenation initially admitted to an outside non–extracorporeal membrane oxygenation center hospital (OSH) then transferred to our extracorporeal membrane oxygenation center (Thomas Jefferson University Hospital (TJUH)). Unstable patients were placed on extracorporeal membrane oxygenation at OSH (Group A) before transport, while others were initiated at our certified extracorporeal membrane oxygenation center (Group B) upon arrival. Group A was further subdivided into patients cannulated by OSH personnel (Group AOSH ) or TJUH transport team (Group ATJUH ). Outcomes and complications were compared between the different initiation sites and personnel. Results: A total of 108 patients were transferred from August 2010 to June 2018. The technical complication rate for all Group A patients was 33/49 (67%), while that of Group B was 24/59 (41%); p = 0.006. Within Group A, Group AOSH had a greater technical complication rate with 29/33 (88%) than Group ATJUH with 4/16 (25%); p < 0.001. extracorporeal membrane oxygenation survival rate was 34/49 (69%) in Group A and 43/59 (73%) in Group B; p = 0.690. The extracorporeal membrane oxygenation survival rate for Group AOSH and Group ATJUH was 21/33 (64%) and 13/16 (81%), respectively; p = 0.210. Conclusion: Promising extracorporeal membrane oxygenation survival rates were observed in transferred patients. The complication rates related to cannulation technique were significantly higher when patients were initiated at non–extracorporeal membrane oxygenation centers, especially when placed by personnel from non–extracorporeal membrane oxygenation centers.